Tinnitus and COVID-19: effect of infection, vaccination, and the pandemic - Tai, Yihsin; Jain, Namitha; Kim, Gibbeum; Husain, Fatima T. (Frontiers in Public Health, 2024)
IntroductionThe COVID-19 pandemic, which began worldwide around March 2020, has had an impact on hearing health, specifically tinnitus and hearing loss. Physiologically, COVID-19 infection, or medication used to treat the infection, has been reported to be a potential risk factor for tinnitus onset. In addition, tinnitus was reported to be a long COVID symptom or to occur after a COVID-19 vaccination in some cases. With most reports focused on the clinical population, this study aimed to investigate how the onset of tinnitus is associated with COVID-19 infection, long COVID, and COVID-19 vaccination in the general population based on self-report, while accounting for otologic and psychological symptoms.MethodsIn this study, a cross-sectional online survey that included general demographic questions, questions about tinnitus, hearing loss, hyperacusis, emotional status, and the Tinnitus Functional Index (TFI) was conducted.ResultsCompleted survey data of 1,511 respondents who reported having tinnitus or believed to have COVID-associated tinnitus were included in the analysis. Participants were categorized into four groups based on their judgment regarding the etiology of their tinnitus: (1) COVID infection group, (2) long COVID group, (3) COVID vaccination group, and (4) pre-existing tinnitus group. The results suggest that tinnitus severity (estimated using TFI scores) was significantly lower in the pre-existing tinnitus group than in any of the COVID-associated tinnitus groups. While varying factors were found to contribute to tinnitus severity among the COVID-associated groups, overall, depression and/or anxiety accounted for the most variance in predicting tinnitus severity.DiscussionThe findings highlight the need to evaluate the impact of varying otologic and psychological symptoms in individuals with COVID-associated tinnitus for better patient-centered care.